The sepoy army in India and its role in the revolution of 1857 ADح6 - كاظم إلهام (Kufa Journal of Arts, 2011)
The commercial expansion of the English East India Company in the Indian subcontinent (1), as a result of the concessions granted to them by the Mughal Emperor Jehan Kerr (1605-1627) (2), and its acquisition of commercial centers in Surat in 1608 and in Masulipatam in 1611, which coincided with With the political trends that outweighed the economic motives and the issuance of the royal decree in 1661 that expanded the powers of the company and authorized it to declare war or peace with any non-Christian prince in the name of the crown (3). And the culmination of the supportive position of the British King Charles II (1660-1685), the company granted the island of Bombay to them in 1668 in exchange for ten pounds as an annual rent (4), noting that the king obtained it as a result of a contract with